Cell Wall Maturation of Arabidopsis Trichomes Is Dependent on Exocyst Subunit EXO70H4 and Involves Callose Deposition. Issue 1 (12th March 2015) - Kulich, Ivan; Vojtíková, Zdeňka; Glanc, Matou¡; Ortmannová, Jitka; Rasmann, Sergio; Žárský, Viktor
Abstract : Arabidopsis trichomes contain an internal callose-rich and autofluorescent cell wall layer, the biogenesis of which is stimulated by UV-B irradiation and is dependent on secretory machinery. Abstract: Arabidopsis ( Arabidopsis thaliana ) leaf trichomes are single-cell structures with a well-studied development, but little is understood about their function. Developmental studies focused mainly on the early shaping stages, and little attention has been paid to the maturation stage. We focused on the EXO70H4 exocyst subunit, one of the most up-regulated genes in the mature trichome. We uncovered EXO70H4-dependent development of the secondary cell wall layer, highly autofluorescent and callose rich, deposited only in the upper part of the trichome. The boundary is formed between the apical and the basal parts of mature trichome by a callose ring that is also deposited in an EXO70H4-dependent manner. We call this structure the Ortmannian ring (OR ). Both the secondary cell wall layer and the OR are absent in the exo70H4 mutants. Ecophysiological aspects of the trichome cell wall thickening include interference with antiherbivore defense and heavy metal accumulation. Ultraviolet B light induces EXO70H4 transcription in a CONSTITUTIVE PHOTOMORPHOGENIC1-dependent way, resulting in stimulation of trichome cell wall thickening and the OR biogenesis. EXO70H4-dependent trichome cell wall hardening is a unique phenomenon, which may be conserved among a variety of the land plants. Our analyses support a concept that Arabidopsis trichome is an excellent model to study molecular mechanisms of secondary cell wall deposition.